Mechanical and physical properties assessment of Bulk Fill resin composites - Rizzante, Fabio Antonio Piola (2018)
The achievement of predictable and long lasting adhesive restorations in posterior teeth have always been a major objective of studies in the context of materials and techniques development. The use of bulk fill composites could provide better outcomes, but it is important to assess their physico-mechanical properties, responsible for their clinical behavior. The purpose of the present study was to assess the mechanical and physical properties of bulk fill composites. The composites were divided into 2 groups according to their viscosity. For low viscosity composites, the present study assessed: Surefill SDR flow (SDR), X-tra Base (XB), Filtek Bulk Fill Flowable (FBF), and Filtek Z350XT Flow (Z3F- control); and for high viscosity composites: Tetric Evo Ceram Bulk Fill (TBF), X-tra Fil (XF), Filtek Bulk Fill (FBP), Admira Fusion x-tra (ADM) and Filtek Z350 XT (Z3XT- control). Composites were assessed through shrinkage stress test (using 12 and 24mm3 of composite in a custom device adapted in an Universal Testing Machine); volumetric shrinkage (using 64mm3 of composite placed on a Teflon mold and scanned in a micro computed tomography/CT); Youngs modulus (through a 3-point bending test device adapted in an Universal Testing Machine); microhardness and depth of cure tests (using longitudinal Knoop microhardness). All data was evaluated regarding their homogeneity using Shapiro-Wilk test. For polymerization stress, 3-way Variance Analysis (ANOVA) was used. Considering Volumetric Shrinkage, Youngs Modulus, Microhardness and Depth of Cure, one-way ANOVA was used. All ANOVA tests were followed by Tukeys test and 5% was adopted as significance level. Shrinkage stress test with 12mm3 showed SDR, TBF and XF generating the lowest stress after 300s, followed by other high viscosity composites (ADM, FBF, XB and FBP/Z3XT). The regular low viscosity composite (Z3F) generated the highest stress for all assessed times. Considering the same test, with 24mm3, after 300s, SDR, FBP and ADM generated similar stress, followed by TBF and XF. Low viscosity bulk fill composites generated lower stress than Z3F. Considering Youngs modulus, low viscosity composites (SDR, FBF, XB and Z3F) showed the lowest values, followed by ADM and TBF. The other high viscosity composites (Z3XT, FBP and XF) showed the highest values. For microhardness test, all low viscosity composites showed lower values (FBF being the lowest). For high viscosity composites, Z3XT showed the highest values, followed by XF, FBP/TBF and ADM. Assessing depth of cure, regular composites showed lower values when compared with bulk fill composites. All bulk fill composites showed adequate depth of cure over 4.5mm (microhardness 80% of initial reading). SDR and XB showed the highest depth of cure. All high viscosity bulk fill composites generated lower volumetric shrinkage than regular composites. All low viscosity bulk fill composites showed similar volumetric shrinkage when compared to the regular composites (Z3F and Z3XT). Bulk fill composites show characteristics that allow their use in larger increments (i.e. volumetric shrinkage and polymerization stress similar or lower when compared with regular composites). Nonetheless, the mechanical properties of bulk fill composites were widely variable, being important to individually assess each material previously to its clinical application.